Denatured acellular dermal matrix seeded with bone marrow mesenchymal stem cells for wound healing in mice. Issue 7 (November 2019) - Qi, Yongjun; Dong, Zhengxue; Chu, Hongzhen; Zhao, Qi; Wang, Xiao; Jiao, Ya; Gong, Hongmin; Pan, Yi; Jiang, Duyin
Highlights: Burn skin after decellularized maintained porous network structure and showed good biocompatibility in vivo . Stem cells in denatured acellular dermal matrix scaffolds survived and proliferated well. Denatured acellular dermal matrix scaffold seeded with stem cells promoted wound healing. The scaffold seeded with stem cells accelerated re-epithelialization, appendages regeneration and neovascularization of wound. Abstract: It is the basic task of burn therapy to cover the wound with self-healthy skin timely and effectively. However, for patients with extensive burns, autologous skin is usually insufficient, and allogenic or heterogeneous skin leads to strong immune response. It is vital to choose an appropriate treatment for deep extensive burns. Nowadays, the dermal substitute combined with bone marrow mesenchymal stem cells (BM-MSCs) is a prospective strategy for burn wound healing. Denatured acellular dermal matrix (DADM), as one of dermal substitutes, which prepared by burn skin discarded in escharotomy, not only maintains a certain degree of 3D structure of collagen, but also has good biocompatibility. In this study, the preparation method of DADM was improved and DADM was seeded with BM-MSCs. Then BM-MSCs-seeded DADM (DADM/MSCs) was implanted into mice cutaneous wound, and the effect of DADM/MSCs dermal substitute was assessed on skin regeneration. As a result, BM-MSCs survived well and DADM/MSCs scaffolds significantly promoted wound healing in terms of angiogenesis, re-epithelialization and skin appendage regeneration. DADM/MSCs scaffold may represent an alternative promising therapy for wound healing in deep extensive burns.